PENGARUH KESEJAHTERAAN TERHADAP KINERJA PEGAWAI INSPEKTORAT KABUPATEN MINAHASA UTARA - BAGO, SYUKURMAN DEARJOY; LENGKONG, FLORENCE DEISY JETTY; TAMPI, GUSTAAF BUDDY (JURNAL ADMINISTRASI PUBLIK, 2018)
This study aims to determine and analyze the effect of welfare on the performance of Minahasa UtaraInspectorate.The research method is a quantitative research method, it is a research method based on thephilosophy of positivism, used to examine the population or a particular sample. The sampling techniqueis a saturated sampling technique in the Inspectorate of Minahasa Utara, there are 38 aparatus. The usingof data analysis techniques are simple linear regression analysis and simple correlation analysis. Based onthe results of analysis using correlation pearson product moment, the outcome of correlation coefficient is(r) = 0,382 while the coefficient of determination is (r²) = 0,146. Based on this research, the hypothesispresented can be accepted that there is a degree of linkage and determination of the welfare to theperformance of apparatus in Inspectorate of Minahasa Utara. Based on the results of the study, it can beconcluded that the welfare has a relationship and has a significant effect on performance of apparatusservice in Inspectorate of Minahasa Utara. This means that welfare is one of the determinants of theimprovement of performance of the apparatus.Keyword: Welfare, Apparatus Performance